2021
DOI: 10.37680/muharrik.v4i02.1082
|View full text |Cite
|
Sign up to set email alerts
|

Managing Digital Fundraising of Dompet Dhuafa During Covid-19 Pandemic

Abstract: Covid-19 pandemic demands zakah institutions to avoid physical contact activities, and outlet openings in public places. A marketing communication strategy is needed to make humanitarian mission and empowerment as zakah institutions’ core products synergize to resolve pandemic social impacts. Dompet Dhuafa, as a zakah institution, has developed fundraising digitalization to deal with the Covid-19 pandemic. This study describes fundraising digitalization as Dompet Dhuafa’s marketing communication strategy durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Specifically, in the context of zakat, the magnitude of the influence of social media on awareness of zakat is because this media can accelerate information exponentially. Social media can facilitate, accelerate and remove barriers to information flow by facilitating the dissemination of information such as institutional credibility to muzakki (Abdullah et al, 2023;Mohd Khalis et al, 2022;Sofiyawati, 2021). It can be concluded that the information submitted by zakat institutions, especially related to transparency, such as appropriate reporting, administrative security and conformity of information, can increase the positive perception and trust of muzakki.…”
Section: Social Media Engagementmentioning
confidence: 99%
“…Specifically, in the context of zakat, the magnitude of the influence of social media on awareness of zakat is because this media can accelerate information exponentially. Social media can facilitate, accelerate and remove barriers to information flow by facilitating the dissemination of information such as institutional credibility to muzakki (Abdullah et al, 2023;Mohd Khalis et al, 2022;Sofiyawati, 2021). It can be concluded that the information submitted by zakat institutions, especially related to transparency, such as appropriate reporting, administrative security and conformity of information, can increase the positive perception and trust of muzakki.…”
Section: Social Media Engagementmentioning
confidence: 99%
“…Majelis Ulama Indonesia (MUI) mengeluarkan fatwa bahwa zakat maal bisa ditunaikan sesegera mungkin tanpa harus menunggu waktu 1 tahun jika telah mencapai nisabnya (Saputra, 2020). Dompet Dhuafa sebagai salah satu lembaga zakat mengambil langkah untuk mengoptimalkan digital fundraising untuk menghimpun zakat (Sofiyawati, 2021), dan memfokuskan penyaluran dana dalam bentuk konsumtif daripada produktif agar kesulitan masyarakat bisa segera teratasi (Mustofa, 2021). LazisNU Kota Metro Lampung mengimplementasikan penanggulangan pandemi covid-19 dengan membuat program tanggap darurat pemberian bantuan bahan pangan dan dana tunai bagi para korban (Ismail, Rohmawati, Rakhmat, & Hidayati, 2021).…”
Section: Pendahuluanunclassified
“…Majelis Ulama Indonesia (MUI) mengeluarkan fatwa bahwa zakat maal bisa ditunaikan sesegera mungkin tanpa harus menunggu waktu 1 tahun jika telah mencapai nisabnya (Saputra, 2020). Dompet Dhuafa sebagai salah satu lembaga zakat mengambil langkah untuk mengoptimalkan digital fundraising untuk menghimpun zakat (Sofiyawati, 2021), dan memfokuskan penyaluran dana dalam bentuk konsumtif daripada produktif agar kesulitan masyarakat bisa segera teratasi (Mustofa, 2021). LazisNU Kota Metro Lampung mengimplementasikan penanggulangan pandemi covid-19 dengan membuat program tanggap darurat pemberian bantuan bahan pangan dan dana tunai bagi para korban (Ismail, Rohmawati, Rakhmat, & Hidayati, 2021).…”
Section: Pendahuluanunclassified